STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MENENGAH DI KOTA BATURAJA - Rani Anwar; Natalia, Titie Syahnaz (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2021)
Micro, small and medium businesses have an important role for the economy in Indonesia. One of them is economic growth in employment and distribution of development results. On the other hand, MSMEs also face various problems, including limited working capital, low quality of human resources, and a lack of mastery in science and technology. Not only that, the lack of clarity about business prospects and planning, and how to market or promote the products being marketed. The method used in this research is descriptive method. The study population is MSMEs in the City of Baturaja. The data collection techniques used are observation, interviews and questionnaires while the data analysis technique uses SWOT analysis and then formulates strategies to overcome them. The purpose of the strategy for development of middle small micro businesses in the City of Baturaja is expected to increase the income so that welfare is also increasing.